Diseño de procesos administrativos para la mejora continua de la compañía CELDIMAC S.A. - Tenelema Ortiz, Adriana Victoria (2019)
The theme selected for this research work was "Design of administrative processes for the continuous improvement of the company CELDIMAC S.A." Chapter 1 mentions the problems that were evident in this research process, such as: inadequate management of accounting and administrative information, ignorance of accounting and tax regulations, lack of communication and responsibility of company officials, all this has prevented making decisions based on technical reports that serve to meet business objectives. In chapter 2 the study antecedents are described; the conceptual and legal bases that sustain the research process……..